ZnO–Ti3C2 MXene Electron Transport Layer for High External Quantum Efficiency Perovskite Nanocrystal Light‐Emitting Diodes. Issue 19 (16th August 2020) - Lu, Po; Wu, Jinlei; Shen, Xinyu; Gao, Xupeng; Shi, Zhifeng; Lu, Min; Yu, William W.; Zhang, Yu
Abstract: 2D transition metal carbides, nitrides, and carbonitrides called MXenes show outstanding performance in many applications due to their superior physical and chemical properties. Herein, a ZnO–MXene mixture with different contents of Ti3 C2 is applied as electron transport layers (ETLs) and the influence of the Ti3 C2 MXene in all‐inorganic metal halide perovskite nanocrystal light‐emitting diodes (perovskite NC LEDs) is explored. The addition of Ti3 C2 makes more balanced charge carrier transport in LEDs by changing the energy level structure and electron mobility of ETL. Moreover, lower surface roughness is obtained for the ETL, thus guaranteeing uniform distribution of the perovskite NCs layer and further reducing leakage current. As a result, a 17.4% external quantum efficiency (EQE) with low efficiency roll‐off is achieved with 10% Ti3 C2, which is a 22.5% improvement compared to LEDs without Ti3 C2 . Abstract : Adding an appropriate amount of Ti3 C2 into the ZnO electron transport layer (ETL) to change the energy level structure and electron mobility of the ETL and further make the carrier transport balanced is explored. The ZnO/TiC ETL‐based red emitting perovskite nanocrystals light‐emitting diodes exhibit an external quantum efficiency of 17.4%.